(3GdOQI GdeVjI hGdYQhS GdeQVjI hGdTLQI GdfHhjI GdoeMeOjIs - (3jhSa Hf MSf Hf CMeO Hf MSf Hf YHO GdgGOj GdUGdMj, LeGd GdOjf, GHf GdeHQO,J (B909 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj ESJNQL ef LhGgQ Ndbg OQJg GdecfhfI hfhQ GdhLhO HEHQGR cfR CfhGQg GdeUhfI s
(3hgPG GdcJGH JJVef GdcdGe Ydi fSH GdfHi Udi Gddg Ydjg hSdes
(3Ke CSeGA YHjOg hCeQGFg hLfhOg hSdGMg hNjdg heQGcHg hZRhGJgs
(3hETJed CjVkG Ydi CSeGA RhLGJg CegGJ GdeDefjf hcd Pdc Ydi Tcd LOGhd heTLQGJ aj ZGjI GdMSf hGdLeGd hbO aQZ GdeDda ef JCdjag SfI (B881(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B108 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B130 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B176 s
Keywords: (3GdJGQjNs